Kindling - Chee, Traci (Harper, an imprint of HarperCollinsPublishers, 2024)
"Once, the war was fought with kindlings--elite, magic-wielding warriors whose devastating power comes at the cost of their own young lives. Now the war is over, and kindlings have been cast adrift--their magic outlawed, their skills outdated, their formidable balar weapons prized only as relics and souvenirs. Violence still plagues the countryside, and memories haunt those who remain. When a village comes under threat of siege, it offers an opportunity for seven kindlings to fight one last time. But war changed these warriors. And to reclaim who they once were, they will have to battle their pasts, their trauma, and their grim fates to come together again--or none of them will make it out alive." --